Power and resistance in an 4.frican society: The Ciskei "losa and the making of South Africa (Historia, 2021)
Power and resistance is an impressive book and one that makes a valuable contribution to South African historical In a historiography as poorly served by regional histories as ours, the publication of a compreheLsive, thoroughly researched and nuanced historical analysis of a particular region is a noteworthy occurrence. Switzer's history of the Ciskei, is to my knowledge, the first regionally focused study to cover the entire span of South African history from pre-colonial times to the recent past. It also represents a rare attempt at synthesis within the revisionist tradition of South African historiography.
Keywords: L. Switzer; Mohamed Adhikari; Historia; power; resistance; Ciskei; South Africa; histography; pre-colonial; Fish and Kei Rivers; Khoi; San; Xhosa; Eastern Cape